Analysis Of Liver Function And Haemoglobin Levels In Pulmonary Tuberculosis Patients With Anti-Tuberculosis Drug - Siregar, Sarinah; Rezekiyah, Sholeh; Karwiti, Witi; Zuhdy, Nasra; Putra, Egy Sunanda (Politeknik Kesehatan Kemenkes Mamuju, 2024)
Tuberculosis (TB) is an infectious disease caused by Mycobacterium Tuberculosis. Today, Tuberculosis disease is still a major health problem and a global health problem, as the leading cause of death in millions of people every year worldwide. The main TB treatments with Drug Anti-tuberculosis are isoniazid, rifampicin, ethambutol, strep-etamycin, and pyrazinamide. Although most Drugs for tuberculosis are acceptable in therapy, they have a toxic potential to affect especially side hepatotoxic reactions. Many studies have reported rifampicin and INH as a cause of cutaneous eruptions, a flu-like syndrome, anemia, respiratory insufficiency, acute renal failure, agranulocytosis, eosinophilia, and thrombocytopenia. The aim of the study is to analyze liver function tests and hemoglobin levels before and after ATD therapy within 3 months in pulmonary tuberculosis patients in 5 Jambi City Health Centers. This research method is observation with a total of 42 respondents (total sampling). All the patients were diagnosed with pulmonary tuberculosis, and no respondents dropped out. Data collection was carried out from January to June 2023. Liver function and Hb levels were evaluated before and after 3 months of taking anti-tuberculosis drugs. Examinations were carried out in the hematology laboratory of the Health Polytechnic of the Ministry of Health, Jambi. Liver function test results are an increase in total bilirubin of 0.23 mg/dl after 3 months of respondents taking anti-tuberculosis drugs, as well as ALT and AST, each of which increased. However, they are still within normal limits. The average hemoglobin level is included in the anemia group, and there is a significant decrease from 11.94 gr/d to 11.21 gr/dl. There is a risk of hepatotoxicity due to consumption of anti-tuberculosis drugs. In contrast to the average hemoglobin levels being below normal before and after therapy, there is a decrease in hemoglobin levels after 3 months of treatment. It is best to check liver function and Hemoglobin levels periodically to detect liver function abnormalities and anemia in pulmonary tuberculosis sufferers during the treatment period.